Protection of timber constructions by using electro osmotic pulsing technology (PLEOT) - Treu, A. (2011)
Timber constructions are often built in combination with other materials such as concrete. These materials can influence the timber construction. Moist concrete can e.g. lead to development of molds which creates an unhealthy living area for people. Furthermore, moisture in wood buildings can negatively affect the wood material, which can lead to negative biological activity in timber and possible reduction of strength properties of timber constructions. The present paper introduces a new innovative method of timber protection and describes the influence of moisture on wood and concrete. The new environmental friendly system for protection of timber has been tested on wood destroying fungi and termites. It can be shown that wood protection by means of electro osmotic pulsing technology can preserve wood in laboratory trials. The wood moisture content is reduced when the protection system is installed. Trials on protected wood against subterranean termites showed lower wood moisture content after test of protected samples compared to untreated samples. However, termite activity could not be reduced to a larger extend as the termite living surroundings were not included. It could be shown that humidity in pores of concrete in cellar walls is reduced using electro osmotic pulsing. The drying of concrete when combined with timber constructions can additionally help to reduce timber degradation as all protection measures that lead to a drier building are positive for fungi and subterranean termite control.